108k views
0 votes
What is the solution for 5x^2-x+6=0

User RaZzLe
by
5.2k points

1 Answer

5 votes

The easiest way to solve this problem is by using the Pythagorean theorem :D

Pythagorean theorem: [-b +- sqrt(b^2 - 4ac)]/2a

5 = a

-1 = b

6 = c

therefore, by plugging these values in!

[-(-1) +- sqrt((-1)^2 - 4(5)(6))]/2(5)

[1 +- sqrt(1 - 120)]/10

Oh so we're using imaginary numbers, so in this case you'll need to know that i = sqrt(-1), so keep this in mind (I can see why this was so difficult)

[1 +- sqrt(119)*i]10

answers:

( 1 + i*sqrt(119) ) / 10

( 1 - i*sqrt(119) ) / 10

User Enoch
by
4.8k points